MANAGEMENT ANALYSIS OF CONSTRUCTION PROJECT CIPAGER CHECK DAM OF KUNINGAN REGENCY - Dian Indra Rosdiana; Saihul Anwar (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2017)
Project management is one important aspect in the application of knowledge, expertise and skills to achieve the goals or objectives that have been determined in order to obtain optimum results in terms of performance, time, quality and safety.This study was conducted to analyze the Check Dam Project Construction Management Cipager River Kuningan start of calculating volume,implementation works, supplies (tools, labor, materials)budget plan, method, barchart, s curve, analysis critical path method and cash flow. The results showed that the budget plan costs incurred to complete the CipagerCheck Dam RiverOf Kuningan RegencyRp. 6.140.922.000,00(Six billion one hundred forty million Nine hundred twenty two thousand rupiah) including 10% VAT. Then by using analysis critical path method, completion takes as long as 25 weeks, or 175 calendar days.